Sequestering effects on and of vacuum decay - Kaloper, Nemanja; Padilla, Antonio; Stefanyszyn, David (American Physical Society, 2016)
We consider phase transitions and their contributions to vacuum energy in the manifestly local theory of vacuum energy sequestering. We demonstrate that the absence of instabilities imposes constraints on the couplings of gravitating and nongravitating sectors, which can be satisfied in a large class of models. We further show by explicit construction that the vacuum energy contributions to the effective cosmological constant in the descendant vacua are generically strongly suppressed by the ratios of space-time volumes of parent and descendant geometries. This means that the cosmological constant in de Sitter descendant vacua remains insensitive to phase transitions which may have occurred in the course of its cosmic history.